Mitochondrial disorders in patients with familial form of MERRF syndrome - A. Sh. Latypov; E. V. Proskurina; S. V. Kotov; O. P. Sidorova; I. A. Vasilenko; D. V. Kassina; A. S. Kotov (Русский журнал детской неврологии, 2024)
MERRF syndrome (myoclonic epilepsy ragged red fibres) belongs to the group of primary mitochondrial diseases and is characterized by a combination of myoclonic epilepsy and the phenomenon of ragged red fibres on muscle biopsy. The aim of this work is to study mitochondrial disorders in patients from a family with MERRF syndrome by determining the cytochemical activity of mitochondrial enzymes in peripheral blood lymphocytes and the level of lactate in the blood. Clinical cases of a 25-year-old sister and a 19-year-old brother with MERRF syndrome with the m.8344A>G variant in MT-TK (tRNA (Lys)) with a blood heteroplasmy level of 50 % in the sister and homoplasmy in the brother are presented. Mitochondrial disorders were assessed by blood lactate levels and cytochemical studies of mitochondrial enzyme activity in peripheral blood lymphocytes. Pre-prandial blood lactate levels were elevated in both patients. After a carbohydrate load, it increased in the sister, and decreased in the brother. The sister had decreased activity of peripheral blood lymphocyte enzymes while taking levetiracetam, 100 mg of coenzyme Q10 and 100 mg of L-carnitine. The dose of energotropic drugs was increased, which led to an increase in the activity of mitochondrial enzymes. The brother had a compensatory increase in the level of succinate dehydrogenase and a decrease in the activity of other enzymes. The methods we used can be used in clinical practice to diagnose mitochondrial disorders and to adjust the dosage of energotropic drugs, which remain relevant due to the lack of effective gene therapy.